Chronic Thromboembolic Pulmonary Hypertension - Piazza, Gregory; Goldhaber, Samuel Z (The New England journal of medicine, 2011)
Chronic thromboembolic pulmonary hypertension can develop after acute pulmonary embolus but is often overlooked until pulmonary hypertension has led to dyspnea and right ventricular dysfunction. This review provides a guide to early diagnosis and management. Chronic thromboembolic pulmonary hypertension is defined as mean pulmonary-artery pressure greater than 25 mm Hg that persists 6 months after pulmonary embolism is diagnosed. The 2008 World Symposium on Pulmonary Hypertension 1 emphasized the importance of chronic thromboembolic pulmonary hypertension, which occurs in 2 to 4% of patients after acute pulmonary embolism. 2 , 3 The frequency of this condition among patients with pulmonary hypertension is unknown. Patients with chronic thromboembolic pulmonary hypertension generally present in their 40s, although this condition has been reported in patients in other age groups. 2 The diagnosis is often overlooked because many patients do not have a history . . .